Factors Associated with DASH Diet Therapy in Blood Pressure Control among the Elderly - Afif Azhar Abulkhair Jayadie; Solikin; Izma Daud (Fakultas Kedokteran, Universitas Papua, 2025)
Hypertension is one of the non-communicable diseases with a high prevalence among the elderly in Indonesia. Efforts to control blood pressure through the Dietary Approaches to Stop Hypertension (DASH) diet therapy are essential; however, various factors are believed to influence its effectiveness at the primary healthcare level. This study aimed to analyze factors associated with DASH diet therapy in blood pressure control among the elderly at the Cempaka Public Health Center, Banjarmasin. This study employed a cross-sectional design with a sample of 188 elderly patients with hypertension selected using purposive sampling. Data were collected using a structured questionnaire covering age, sex, educational level, and dietary adherence, as well as data on the frequency of healthcare visits obtained from patients’ medical records. Blood pressure measurements were conducted after the implementation of the DASH diet for 30 days. Data analysis was performed using the Spearman Rank correlation test with a significance level of α = 0.05. The results showed significant associations between age (p = 0.000), sex (p = 0.000), educational level (p = 0.000), dietary adherence (p = 0.000), and frequency of healthcare visits (p = 0.000) with DASH diet therapy in blood pressure control. Age, sex, educational level, dietary adherence, and frequency of healthcare visits significantly influenced the success of DASH diet therapy.